Manajemen Perioperatif Pembedahan Video-Assisted Thoracoscopy (VATS) Dekortikasi dan Biopsi Pada Pasien dengan Kecurigaan Keganasan Paru Kiri dengan Atrial Septal Defect - Yuliana, Astrid; Dewi, Dewa Ayu Mas Shintya; Aribawa, I Gusti Ngurah Mahaalit (Syntax Literate, 2025)
Video-Assisted Thoracoscopy (VATS) is a minimally invasive procedure that can reduce postoperative pain, shorter hospitalizations, and faster recovery. The use of Double Lumen Tube (DLT) in this procedure is with the aim of optimizing the visualization of the surgical field. However, patients with cardiac disorders, such as Atrial Septal Defect (ASD) that can lead to shunt disorders, require adjustments to anesthesia management in terms of ventilation, especially in preventing shunts from right to left. Case Report. The male patient, 30 years old, came in with massive exudative pleural effusion and a history of ASD Secundum. The patient showed significant weight loss and spirometry results showed pulmonary restriction. Preoperative evaluation showed ASA III, with a risk of respiratory and cardiovascular impairment. Anesthesia is performed with left DLT for OLV and thoracic epidural for multimodal analgesation. Postoperatively, the patient is admitted to the ICU on a ventilator and given analgesia via an epidural. Postoperative monitoring showed stable hemodynamics. Discussion. VATS allows thoracic surgery with minimal incision, reducing postoperative pain and speeding up recovery. DLT selection is important for OLVs that require single-lung ventilation, taking into account risk factors such as ASD that can lead to hemodynamic disorders. Anesthesia management in patients with ASD needs to consider cardiac shunt and pulmonary and systemic blood vessel resistance. The anesthesia technique in VATS can be general anesthesia with ventilation of one lung, accompanied by an epidural block for analgesia. Conclusion. Anesthesia management in patients with ASD undergoing VATS requires special attention to ventilation in order to prevent shunts in the heart and pulmonary and systemic blood vessel resistance.